INTERRELATIONSHIPS AMONG YIELD AND YIELD CONTRIBUTING TRAITS IN CHICKPEA (Cicer arietinum L.) - Fiaz, Sajid; Aslam, Muhammad (Bangladesh Journal of Plant Breeding and Genetics, 2015)
Twenty chickpea genotypes including four varieties were evaluated for the existence of genetic variability and to know the interrelationship among yield traits under study during 2013-2014, at University of Agriculture, Faisalabad. The experiment was carried out in a randomized complete block (RCB) design with three replications. Data were recorded on number of days taken to flowering, number of primary branches plant-1, number of secondary branches plant -1, plant height, number of days taken to maturity, number of pods plant -1, numbers of seed pods-1, total plant weight, Number of grains plant-1, 100- seed weight and grain yield plant-1. The obtained data were analyzed for genetic variability parameters, correlation and path coefficient analysis. The height broad sense heritability estimates were obtained for 100-seed weight (0.977), plant height (0.971), total plant weight (0.971) and number of primary branches plant-1. Genetic advance was higher for plant height (9.054), total plant weight (9.054), number of pods plant-1 (6.414) and 100-seed weight (2.941). The phenotypic coefficient of variation (PCV) was invariably slightly higher than their corresponding genetic coefficient of variation (GCV) due to influence of environment on character expression. Heritability estimates were higher for all characters except number of days taken to maturity and number of grains per plant, which exhibited moderate heritability. Hundred seed weight, plant height, total plant weight and primary branches per plant would be the suitable selection criteria to accomplish better grain yield in chickpea.